Determinants of Consumer Loyalty at Market Place - Rudy Haryanto; Nur El Ikhsan; Iswahyu Pranawukir; Nirstyo Wahdi; Rudi Kurniawan (Yayasan Riset dan Pengembangan Intelektual, 2024)
In the midst of intense competition, e-commerce companies must be astute in seeing every opportunity to grow and effectively create new breakthroughs so that people do not move and continue to make transactions with the company. One way to develop a buying and selling business rapidly nowadays is to sell herbal herbal products online, both from social media and on e-commerce buying and selling platforms. The aim of this research is to analyze and test the influence of service quality, customer experience and trust on the loyalty of herbal medicine consumers who have shopped online on the Lazada marketplace. This research uses quantitative methods with multiple regression analysis. Sampling applied a purposive sampling method and the number of samples in this research was 87 respondents obtained by distributing online questionnaires via WhatsApp to online herbal medicine consumers in the Lazada marketplace. Consumers know the Lazada marketplace and have purchased herbal medicine online on the Lazada marketplace at least 3 times. Data were analyzed using IBM SPSS version 26 through several tests, namely: validity test, reliability test, classical assumption test, multiple linear regression analysis and coefficient of determination test. The results of this research show that service quality, customer experience and trust have a positive and significant effect, both partially and simultaneously, on the loyalty of herbal medicine consumers who have shopped online on the Lazada marketplace. It is hoped that Lazada will further adjust the menu displayed in its application according to needs in order to increase consumer confidence. This can be done by changing the appearance of the application to add to a good shopping experience for consumers.